Self-injury and the embodiment of solitary confinement among adult men in Louisiana prisons - David H. Cloud; Brie Williams; Regine Haardöerfer; Justin T. Hosbey; Hannah L.F. Cooper (Elsevier, 2023)
Solitary confinement is a harrowing human rights and public health problem that is currently inflicted as a routine punishment for a litany of prison rule violations, a reactionary tactic to quell resistance to prison conditions, and as a destination of last resort for people serious mental illnesses (SMI) who are especially vulnerable to its harms. An extensive body of research has documented clusters of psychiatric symptoms-emotional distress, cognitive deficits, social withdrawal, anxiety, paranoia, sleeplessness, and hallucinations-linked to solitary confinement that often manifest in decompensating behaviors, which include self-injury and suicide. This study summarizes the historical evolution of solitary confinement, recaps its linkages to self-injury and suicidality, and offers a theoretical framework grounded in ecosocial theory, and supplemented with concepts from theories of dehumanization and carceral geography. Findings bolster extant evidence on the harms of solitary confinement by focusing on whether and how exertions of power by prison staff to deploy mechanisms of dehumanization-as a pathway between SMI and self-injury among a cross section of adult men (n = 517) exposed to solitary confinement in Louisiana prisons in 2017. Findings reinforce the need for structural interventions that diffuse forms of carceral power and practices that continue to subject people to isolation, dehumanization, and violence.